TRPM7 promotes the metastatic process in human nasopharyngeal carcinoma. Issue 2 (28th January 2015) - Chen, Jian-Peng; Wang, Jun; Luan, Yi; Wang, Cai-Xia; Li, Wen-Huan; Zhang, Jin-Biao; Sha, Dan; Shen, Rong; Cui, Yan-Gang; Zhang, Zheng; Zhang, Li-Ming; Wang, Wei-Bo
Highlights: The function of TRPM7 in nasopharyngeal carcinoma (NPC) has remained uncertain. TRPM7 was closely associated with high metastasis and mortality in NPC patients. TRPM7 was also found to promote invasion and migration of NPC cells. TRPM7 might be a novel prognostic and metastasis-related indicator for patients with NPC. Abstract: Our study observed the relationship between transient receptor potential melastatin 7 (TRPM7) expression and the metastatic process of nasopharyngeal carcinoma (NPC). We found that TRPM7 was overexpressed in 102 out of 206 (49.5%) human NPC cases and was significantly associated with clinical stage and lymphatic and distant metastasis. The results suggested that TRPM7 promotes NPC cell migration and invasion in vitro. Further, TRPM7 was correlated with poor clinical outcome and was an independent predictor for 5-year overall survival rate (HR, 1.832; 95% CI, 1.237–4.146 [P = 0.041]). In conclusion, TRPM7 promotes the metastasis of NPC and may serve as a prognostic marker in NPC patients.